Isolation of Bacteria Causing Urinary Tract Infections and their Antibiotic Susceptibility Profile at Anwer Khan Modern Medical College Hospital - Shilpi, T; Ahmed, MN; Huq, SM Ariful; Baul, SK; Khatun, M (Anwer Khan Modern Medical College Journal, 2013)
Among hospitalized patients, the most common nosocomial infection is Urinary tract infection (UTI). The knowledge about the type of pathogens responsible for UTI and susceptibility and resistance pattern of the causative agents at a specific area may help the doctors to choose correct treatment regimen. This study was aimed to investigate the antibiotic susceptibility and resistance pattern of isolated urinary pathogens. This study was done at Anwer Khan Modern Medical College Hospital, Dhaka during January- June, 2011. Out of 498 clinical samples of urine collected, 245 (49.19%) showed significant bacterial growth. The most common pathogens isolated were Escherichia coli (142, 58.0%), Streptococcus feacalis (38, 15.5%), Pseudomonus (20, 8.2%), Klebsiella species (20, 8.2%) and Staphylococcus epidermidis (14, 5.7%). Members of the Enterobacteriaceae were 75%-100%sensitive to Amikacin and Nitrofurantoin while they were found variably sensitive to other commonly used antibiotics. Pseudomonas species were found 90% sensitive to Meropenem and 70% to Amikacin. Strep. feacalis were found 94.7% sensitive to Amoxicillin, 84.2% to Amoxiclave and 78.9% to Ciprofloxacin, 65.5% to Cephalexin, 50% to Ceftriaxone. The clinicians should use Meropenem and Amikacin selectively in cases of un-responsiveness to commonly used antibiotics. Anwer Khan Modern Medical College Journal Vol. 4, No. 2: July 2013, Pages 23-27 DOI: http://dx.doi.org/10.3329/akmmcj.v4i2.16938